Perceived discrimination of highly educated Latvian women abroad - Inese Šūpule (Administrative Sciences, 2021)
The aim of this paper is to answer the question of what factors lead to an increase in perceived discrimination in the workplace among highly educated Latvian women abroad. Although highly educated migrant women are privileged with regard to education, nonetheless, they face discrimination, lower wages, inferior working conditions, de-skilling and brain waste while working abroad. Based on the discussion on the relationship between sociocultural integration and discriminatory practices or perceived discrimination, and two competing theoretical propositions regarding the effects of integration on perceptions and experiences of discrimination, the article tests if attachment to the host country is related to perceived discrimination at work. The data source used for the analysis is a subsample of a quantitative survey of Latvian emigrants. The subsample (n = 2332) includes Latvian women with a tertiary education who are first-generation emigrants from Latvia and who were working at the time of the survey. Results from binary logistic regression analyses reveal that a low attachment to the host country, financial difficulties coping with daily expenses, problems with recognition of an education certificate and lack of a written contract with the employer increase the likelihood of highly educated Latvian women abroad to claim unfair treatment in the workplace.
Keywords: 350; perceived discrimination; highly skilled women; labor migration; Latvia